2018
DOI: 10.1152/jn.00033.2018
|View full text |Cite
|
Sign up to set email alerts
|

Movement vigor as a traitlike attribute of individuality

Abstract: A common aspect of individuality is our subjective preferences in evaluation of reward and effort. The neural circuits that evaluate these commodities influence circuits that control our movements, raising the possibility that vigor differences between individuals may also be a trait of individuality, reflecting a willingness to expend effort. In contrast, classic theories in motor control suggest that vigor differences reflect a speed-accuracy trade-off, predicting that those who move fast are sacrificing acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
102
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(112 citation statements)
references
References 72 publications
10
102
0
Order By: Relevance
“…We thus investigated the influence of peak velocity, peak acceleration and variable trajectory errors throughout adaptation or specifically during the early and late phases of Prism exposure (first and last 10 exposure trials). We found that interlimb transfer was correlated with variables typically associated to movement vigor, such as peak acceleration and peak velocity (Mazzoni et al 2007;Reppert et al 2018). Figure 8A shows a positive linear correlation between the transfer value and the mean peak acceleration averaged across the Prism exposure phase (PA = 0.1 × transfer value -6; r=0.52; p=0.02).…”
Section: Individual Kinematic Features Correlate With the Interlimb Tmentioning
confidence: 80%
See 1 more Smart Citation
“…We thus investigated the influence of peak velocity, peak acceleration and variable trajectory errors throughout adaptation or specifically during the early and late phases of Prism exposure (first and last 10 exposure trials). We found that interlimb transfer was correlated with variables typically associated to movement vigor, such as peak acceleration and peak velocity (Mazzoni et al 2007;Reppert et al 2018). Figure 8A shows a positive linear correlation between the transfer value and the mean peak acceleration averaged across the Prism exposure phase (PA = 0.1 × transfer value -6; r=0.52; p=0.02).…”
Section: Individual Kinematic Features Correlate With the Interlimb Tmentioning
confidence: 80%
“…We found that peak acceleration and peak velocity during prism exposure, as well as variability of initial direction at the end of the exposure phase, were related to interlimb transfer. Mazzoni et al (2007) as well as Reppert et al (2018) highlighted how variables related to movement vigor, peak velocity or peak acceleration, for instance, vary across individuals, possibly because of differences in perceived motor cost. Kitazawa et al (1997) previously highlighted the importance of peak velocity in prism adaptation when they showed that the magnitude of the after-effect depends on the velocity difference between movements during and after the exposure phase (see also Mattar & Ostry 2010).…”
Section: On the Correlation Between Kinematic Variables Interlimb Trmentioning
confidence: 99%
“…For the 10p and 50p trials participants could earn money based on their combined reaction time and movement time. The scoring function which translated performance to monetary gain was adaptive (figure 1B), factoring in the recent history of movement times and reaction times to ensure participants experienced comparable amounts of reward despite idiosyncrasies in individual’s reaction times and movement speed (Berret et al, 2018; Reppert et al, 2018; Manohar et al, 2015). To assess selection and execution performance concomitantly, we interleaved normal trials and distractor trials.…”
Section: Resultsmentioning
confidence: 99%
“…The reward function was a close-loop design that incorporated the recent history of performance, to ensure that participants received similar amounts of reward, and that the task remained consistently challenging over the experiment (Manohar et al, 2015; Reppert et al, 2018). To that end, the reward function was defined as: where r max was the maximum reward value for a given trial, MTRT the sum of reaction time and movement time, and τ 1 and τ 2 adaptable parameters varying as a function of performance (figure 1B).…”
Section: Methodsmentioning
confidence: 99%
“…Execution of reaching movements also showed a pronounced increase in peak velocity (vigour) with reward, while radial accuracy was maintained. While these reward-driven improvements are now behaviourally wellcharacterised and confirmed in a number of previous reports (Griffiths and Beierholm 2017;Reppert et al 2018;Summerside et al 2018), the neural substrates of these effects remain unknown. Here, we aimed to investigate which cortical regions are involved in the reward-based enhancement of motor performance using transcranial magnetic stimulation (TMS).…”
Section: Introductionmentioning
confidence: 62%